(hkl)-Specific defects of MgO–CoO alloy produced by pulsed laser ablation in water. Issue 43 (8th October 2015) - Chen, Bang-Ying; Lin, Shih-Siang; Shen, Pouyan; Chen, Shuei-Yuan
Abstract : MgO–CoO particles with ( hkl )-specific paracrystalline defects by pulsed laser ablation of solid-solution powders in water. Abstract : Metal oxides with ( hkl )-specific defects of rocksalt-type based structure were fabricated by pulsed laser ablation of powdery MgO–CoO alloy (molar ratio 9 : 1, 5 : 5, 1 : 9 denoted as M9C1, M5C5 and M1C9, respectively, against CoO) in water and characterized using transmission electron microscopy. The resultant submicron-sized particles have a well-developed 100 surface with 110 edges and abundant dislocations for M9C1, whereas a rough surface and paracrystalline distribution of defect clusters ( ca. 1.5–2 nm interspacing) along with spinel-type intergrowth for Co-richer compositions were obtained. Such paracrystals tended to form arrays following the 111 vicinal planes of the rocksalt-type host, i.e. 112 and 113 for M5C5 and 115 for Co1− x O, under the influence of a mutual dopant and/or the hydrogenation effect. A stable [110](1̄11)/(1̄12) asymmetrical tilt boundary with a fair coincidence site lattice also occurred by 111-specific coalescence of the spinel particles for the M1C9 specimen. The composition-dependent formation of paracrystalline distribution of defect clusters and internal compressive stress (up to ca. 1 GPa) of the rocksalt-type host with characteristic UV absorbance are addressed.